Enhancement of Hypoxia Tolerance of Gibel Carp (Carassius auratus gibelio) via a Ferroporphyrin-Rich Diet - Hualiang Liang; Haifeng Mi; Kai Wang; Mingchun Ren; Lu Zhang; Dongyu Huang; Jiaze Gu (Antioxidants)
Gibel carp (Carassius auratus gibelio) were hypoxia stressed for 12 h after an 8-week FPR nutrient-enriched feeding experiment, which was to evaluate the role of FPR in hypoxic stress in gibel carp (Carassius auratus gibelio). The dissolved oxygen was reduced to a range of 0.6 ± 0.2 mg/L. Results showed that FPR supplementation could maintain the osmotic pressure equilibrium by improving the ion concentrations of plasma including Na+, Ca+ and K+, and Na+/K+-ATPase activity of liver. FPR supplementation could effectively enhance the antioxidant capacity by improving the levels of GPX, SOD, CAT, and GSH, and reduce the level of MDA. FPR supplementation could improve the core gene expressions of Nrf2 signalling pathway including nrf2, sod, ho-1, gpx, and cat. The high levels of FPR supplementation (0.04%) might had a negative effect on immunity. FPR supplementation could improve the expression levels of HIF-1 signalling pathway-related genes to adapt to hypoxia condition including hif-1α, epo, angpt1, vegf, et1, and tfr-1. These results also were supported by higher SR and number of gill mitochondria in FPR supplementation. In general, the appropriate FPR supplementation was 0.01% based on the results of this study and economic cost, which could heighten hypoxic adaptation and SR.